1993
DOI: 10.1038/jcbfm.1993.102
|View full text |Cite
|
Sign up to set email alerts
|

Secobarbital Attenuates Excitotoxicity but Potentiates Oxygen—Glucose Deprivation Neuronal Injury in Cortical Cell Culture

Abstract: Summary:We examined the effects of secobarbital and other sedative-hypnotic barbiturates on the neuronal death induced by exposure to excitatory amino acids or deprivation of oxygen or glucose in mouse cortical cell cultures. N-Methyl-D-aspartate (NMDA), a-amino-3-hydroxy-5-methyl-4-isoxazolepropionate, and kainate toxicities were attenuated in a concentration-dependent fashion by high concentrations of secobarbital or thiopen tal. Antagonism of NMDA toxicity was not overcome by increasing NMDA concentration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…As expected from previous reports (Choi et al, 1987;Giffard et al, 1993;Black et al, 1995), NMDA was potently toxic for mature (12-15 days in vitro) cortical neurons. In control cultures, >95% of the neurons were alive at 12-15 days ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…As expected from previous reports (Choi et al, 1987;Giffard et al, 1993;Black et al, 1995), NMDA was potently toxic for mature (12-15 days in vitro) cortical neurons. In control cultures, >95% of the neurons were alive at 12-15 days ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…35 A potential mechanism is blockade of glutamate receptors, including the kainate, N-methyl-D-aspartate (NMDA), and -amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) sub-types. 36 Relevant to the present results is the data of Cai et al, 37 who observed a differential ability, in a neuronal culture, of barbiturates to block these receptors.…”
Section: Glutamatementioning
confidence: 99%
“…These actions suggest that barbiturates should effectively reduce excitotoxic neuronal injury, particularly under conditions of energy deprivation. Therefore, it is surprising that barbiturates do not attenuate neuronal death in cell-culture models of glucose or combined oxygen-glucose deprivation (Giffard et al, 1993) that produce NMDA receptor-dependent toxicity.…”
mentioning
confidence: 99%